2017
DOI: 10.1155/2017/5080128
|View full text |Cite
|
Sign up to set email alerts
|

Bioenergetic Changes during Differentiation of Human Embryonic Stem Cells along the Hepatic Lineage

Abstract: Mitochondrial dysfunction has been demonstrated to result in premature aging due to its effects on stem cells. Nevertheless, a full understanding of the role of mitochondrial bioenergetics through differentiation is still lacking. Here we show the bioenergetics profile of human stem cells of embryonic origin differentiating along the hepatic lineage. Our study reveals especially the transition between hepatic specification and hepatic maturation as dependent on mitochondrial respiration and demonstrates that e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 25 publications
2
10
0
Order By: Relevance
“…No significant differences were detected after 168 h compared to controls ( Figure 4G). These results are in accordance with the minor dependence on OXPHOS observed in mature cells [69][70][71].…”
Section: Glycolytic and Oxphos Profiles During Atra-induced Nb4 Diffesupporting
confidence: 90%
“…No significant differences were detected after 168 h compared to controls ( Figure 4G). These results are in accordance with the minor dependence on OXPHOS observed in mature cells [69][70][71].…”
Section: Glycolytic and Oxphos Profiles During Atra-induced Nb4 Diffesupporting
confidence: 90%
“…Our data suggest a role for IRF4-mediated MERTK signaling in CD8 þ T-cell mitochondrial respiration, which is necessary for T CM differentiation and longevity (39,40). We have previously shown that the bioenergetics of even close differentiation stages can differ in their activity of glycolysis and oxidative phosphorylation (41). The downregulation of IRF4 and the change in bioenergetic phenotype demonstrated after anti-PROS1 treatment indicates a shift in differentiation stage of CD8 þ T cells.…”
Section: Discussionmentioning
confidence: 59%
“…Multiple protocols have been developed to differentiate iPSCs to hepatocyte-like cells, and the resulting cells express hepatic markers and exhibit many functions associated with hepatocytes ( Si-Tayeb et al, 2010 ; Touboul et al, 2010 ). Researchers have previously examined mitochondrial maturation during the formation of iPSC-derived hepatocytes and confirmed an increase of mtDNA copy number, mitochondrial gene expression, cristae structure, and oxygen consumption in iPSC-derived hepatocytes compared with undifferentiated cells ( Yu et al, 2012 ; Hopkinson et al, 2017 ). The high metabolic activity of hepatocytes makes them especially dependent on efficient mitochondrial function to provide ATP, while iPSCs rely largely on glycolysis as the source of energy production ( Folmes et al, 2011 ; Zheng et al, 2016 ).…”
Section: Resultsmentioning
confidence: 89%